De oostpartij van de tiende-eeuwse Sint-Lambertuskathedraal van Luik als navolging van de Dom van Keulen (Bulletin KNOB, 1997)
St. Lambertus Cathedral at Liège, renovated by Bishop Notger (972- 1008), was consecrated in 1015. After a fire in 1185 the church was largely rebuilt in Gothic style. This church was demolished after the French occupation at the end of the eighteenth century. In 1907 a research of the pre-Romanesque Cathedral was carried out in which the church was excavated from the west side.The eastern part was not laid bare until in the seventies. The church turned out to have had a semicircular eastern apsis, flanked by two apsidioles. One of the conclusions of the research was that the pre-Romanesque Cathedral did not have an eastern crypt, though a western crypt dating from this period was indeed found.However, renewed consideration of the excavation data proves that an eastern crypt could not have been found, since the entire surroundings of the crypt were rebuilt during the renovation at the end of the twelfth century. Moreover, the discovery of a fortifying wall indicates activities performed from the crypt. Written sources on a possible crypt are scarce.The major source in this case is the Gesta Episcoporum Leodiensium of Gilles van Orval. The chronicle was compiled in the thirteenth century, making use of the existing sources. However, the source of the passage in which Gilles refers to the eastern crypt, the crypta inferior cannot be traced. Nevertheless Gilles generally is a reliable authority. The pre-Romanesque St. Lambertus of Liège resembles the Cathedral of Cologne in many respects.The excavations proved that both churches had similar types of apsides. Both also had two transepts. As the apsis at Liège had actually passed out of use at the time when it was built, the choice of the architect must have had a particular meaning. It is obvious that he may have wished to refer to the Cathedral of Cologne. The reason of this reference can be interpreted in various ways. It has been suggested that Notger's church can be seen as a manifesto of the recently established power of the Ottonians in politically unstable Lotharingia.On the other hand, the fact that Notger was capable of building a large cathedral can in itself be seen as a convincing sign of his and the German emperor's power. Motives for the renovation of the church at Liège may have been the dilapidated state of its predecessor and the church as a sign of the power and ambition of the bishop.